Serum iron is closely associated with metabolic dysfunction-associated fatty liver disease in type 2 diabetes: A real-world study - Wang, Jun-Wei; Jin, Chun-Hua; Ke, Jiang-Feng; Ma, Yi-Lin; Wang, Yu-Jie; Lu, Jun-Xi; Li, Mei-Fang; Li, Lian-Xi (Frontiers in Endocrinology, 2022)
Aims: There is still a debate about the relationship between serum iron and metabolic dysfunction-associated fatty liver disease (MAFLD). Furthermore, few relevant studies were found in type 2 diabetes mellitus (T2DM). Therefore, this study aims exploring the association of serum iron levels with MAFLD in Chinese patients with T2DM. Methods: This cross-sectional, real-world study composed 1467 Chinese T2DM patients. MAFLD was diagnosed by abdominal ultrasonography. Depending on serum iron quartiles, the patients were classified into four groups. Clinical characteristics were compared among the four groups and binary logistic analyses were used to assess the associations of serum iron levels and quartiles with the presence of MAFLD in T2DM. Results: After adjusting for gender, age, and diabetes duration, significantly higher prevalence of MAFLD was found in the second (45.7%), third (45.2%), and fourth (47.0%) serum iron quartiles than in the first quartiles (25.9%), with the highest MAFLD prevalence in the fourth quartile (P < 0.001 for trend). Moreover, increased HOMA2-IR (P = 0.003 for trend) as well as decreased HOMA2-S (P = 0.003 for trend) were observed across the serum iron quartiles. Fully adjusted binary logistic regression analyses indicated that both increased serum iron levels (OR: 1.725, 95% CI: 1.427 to 2.085, P < 0.001) and quartiles (P < 0.001 for trend) were still closely associated with the presence of MAFLD in T2DM patients even after controlling for multiple confounding factors. Conclusions: There is a positive correlation between the presence of MAFLD and serum iron levels in T2DM patients, which may attribute to the close association between serum iron and insulin resistance. Serum iron levels can act as one of the indicators for evaluating the risk of MAFLD in T2DM individuals.